2007
DOI: 10.1890/0012-9658(2007)88[424:cvsfil]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Climate vs. Soil Factors in Local Adaptation of Two Common Plant Species

Abstract: Evolutionary theory suggests that divergent natural selection in heterogeneous environments can result in locally adapted plant genotypes. To understand local adaptation it is important to study the ecological factors responsible for divergent selection. At a continental scale, variation in climate can be important while at a local scale soil properties could also play a role. We designed an experiment aimed to disentangle the role of climate and (abiotic and biotic) soil properties in local adaptation of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 45 publications
6
143
1
Order By: Relevance
“…The higher seedling survival on soil from restoration sites may be due to a lower abundance of pathogenic fungi in soils that were used for arable practice and where no C. jacea has grown for many years, and the negative feedback may be less strong in those soils than in soils from late-successional grasslands, where the soil microbial community may have been cultured by the presence of C. jacea. (Klironomos 2002;De Deyn et al 2003;Kardol et al 2006;Bezemer et al 2006;Macel et al 2007). However, various other groups of soil organisms can also affect seedling survival, including root feeding insects and nematodes (Brown and Gange 1989;Olff et al 2000;De Deyn et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The higher seedling survival on soil from restoration sites may be due to a lower abundance of pathogenic fungi in soils that were used for arable practice and where no C. jacea has grown for many years, and the negative feedback may be less strong in those soils than in soils from late-successional grasslands, where the soil microbial community may have been cultured by the presence of C. jacea. (Klironomos 2002;De Deyn et al 2003;Kardol et al 2006;Bezemer et al 2006;Macel et al 2007). However, various other groups of soil organisms can also affect seedling survival, including root feeding insects and nematodes (Brown and Gange 1989;Olff et al 2000;De Deyn et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Becker, Colling, Dostal, Jakobsson, & Matthies 2006;Etterson 2004;Joshi et al 2001). Climate has been identified as the main driver of selection at such large scales but other environmental factors that show large-scale patterns may also act as diverging selective forces (Etterson 2004;Joshi et al 2001;Macel et al 2007;Santamaria et al 2003). In addition, the probability of gene flow and genetic exchange between populations decreases with distance enhancing genetic differentiation even if environmental conditions and selective forces are very similar (Epperson 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a reciprocal transplant study comparing local adaptation of grass species (which 20 are not directly affected by nitrogen-fixing bacteria) and legumes (which are directly affected by nitrogen-fixing bacteria) found that grass species were primarily locally adapted to climatic conditions, whereas legumes performed much better when grown in their local soil (Macel et al 2007). Similarly, a study of bacterial local adaptation to soil from across an old growth forest demonstrated a decrease in fitness as bacteria were 25 transplanted away from their home site at a rate of about six percent per meter; a rate which is similar in scale to plant local adaptation (Belotte et al 2003).…”
Section: Bacterial Local Adaptationmentioning
confidence: 99%